Migration among the First Nations: Reflections of inequalities - Amorevieta-Gentil, Marilyn; Bourbeau, Robert; Robitaille, Norbert (Scholarship@Western, 2016)
The subject of this review is the migration dynamics of the First Nations (Registered and non-registered Indians), seen in the light of inequalities of various kinds. Individuals who undertake a migration are attempting to find a balance between their current situation and the situation they would like to be in, with a view to a better life. Analysing these situations implies making decisions which lead them to opt for the type of migration likely to bring them most benefit. The First Nations are a distinct population group in Canada. As well as being heterogeneous, they also have their own socio-demographic, cultural and political characteristics, and these lie behind some types of migration flows which are unique to Canada. The different inequalities the First Nations experience also need to be better understood, if they are to be more effectively reduced. The nature, intensity and direction of the migration flows of the First Nations (Registered and non-registered Indians) reflect these inequalities, both between their communities, and also between them and the non-Aboriginal population. The most common form of First Nations migration is residential mobility, either within the same community or within an urban centre, whereas inter-provincial and international migration is rare. The net effect of the migration among Registered Indians is mainly towards the reserves, rather than to other rural or urban areas. The quest for better living conditions and the feeling of belonging to a community are the most frequent explanations for Indians deciding to migrate. These migrations may benefit Indian communities in some cases and in others may disadvantage them.